We Go through a Bit of Everything”: The Labyrinth Career of the Professional Trajectories of Executive Women - Vaz, Duarte Rabelo, Elem; Gallon, Shalimar; Fraga, Mendonça, Aline (Review of Business Management, 2023)
Purpose – The present study aimed to analyze the perception of executive women about the barriers experienced in their professional trajectory. Design/methodology/approach – Using a descriptive and qualitative approach, 30 Brazilian executive women were interviewed and the data were analyzed through content analysis. Findings – Obstacles in the advancement of women’s careers permeate sociocultural and organizational relationships, as well as family relationships. The results indicate that during their professional trajectory, executives face different barriers that configure their careers as a labyrinth. The coined term of “career labyrinth” is marked by the various (re)entries and instabilities promulgated by stereotypes, prejudices, discrimination and the use of oppressive resources of gender such as mansplaining, manterrupting, bropriating, gaslighting and harassment, which are perceived, silenced, negotiated and faced. Originality/value – The study shows the urgency of building programs aimed at the professional advancement of women in organizations, especially in spaces historically occupied by men. It encourages reflections on human resource management policies that can promote gender equality in executive positions through practices that value and encourage the participation of women in organizational spaces, considering their possible particularities. Keywords – career; woman; barriers; stereotype; labyrinth.